Quantitative characterization of adhesion and stiffness of corneal lens of Drosophila melanogaster using atomic force microscopy. (January 2016) - Lavanya Devi, A.L.; Nongthomba, Upendra; Bobji, M.S.
Abstract: Atomic force Microscopy (AFM) has become a versatile tool in biology due to its advantage of high-resolution imaging of biological samples close to their native condition. Apart from imaging, AFM can also measure the local mechanical properties of the surfaces. In this study, we explore the possibility of using AFM to quantify the rough eye phenotype of Drosophila melanogaster through mechanical properties. We have measured adhesion force, stiffness and elastic modulus of the corneal lens using AFM. Various parameters affecting these measurements like cantilever stiffness and tip geometry are systematically studied and the measurement procedures are standardized. Results show that the mean adhesion force of the ommatidial surface varies from 36 nN to 16 nN based on the location. The mean stiffness is 483±5 N/m, and the elastic modulus is 3.4±0.05 GPa (95% confidence level) at the center of ommatidia. These properties are found to be different in corneal lens of eye expressing human mutant tau gene (mutant). The adhesion force, stiffness and elastic modulus are decreased in the mutant. We conclude that the measurement of surface and mechanical properties of D. melanogaster using AFM can be used for quantitative evaluation of 'rough eye' surface. Graphical abstract: Highlight: Using AFM adhesion force and stiffness of the eye of the fruit fly are measured. Effect of AFM probe shape and stiffness on these measurements are studied. It is shown that AFM can be used to distinguish "Rough eye" phenotype.